#### Answer

3

#### Work Step by Step

$f(x)=2x^2-x$
Substitute $-1$ to $x$ to obtain:
$f(-1)=2(-1)^2-(-1)=3$

Published by
Pearson

ISBN 10:
0-32197-907-9

ISBN 13:
978-0-32197-907-0

3

$f(x)=2x^2-x$
Substitute $-1$ to $x$ to obtain:
$f(-1)=2(-1)^2-(-1)=3$

You can help us out by revising, improving and updating this answer.

Update this answerAfter you claim an answer you’ll have **24 hours** to send in a draft. An editor
will review the submission and either publish your submission or provide feedback.